2008
DOI: 10.1016/j.ecresq.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The relations among young children's peer-reported trustworthiness, inhibitory control, and preschool adjustment

Abstract: Sixty-five (38 male and 27 female) preschool children (mean age = 5 years 1 month) completed measures of peers' trustworthiness (promise keeping and secret keeping). Teachers rated the preschool children's inhibitory control, trustworthiness, and preschool adjustment. Structural Equation Modeling (SEM) yielded support for the hypothesized model. The expected positive paths were found from (1) gender to preschool adjustment and inhibitory control, (2) age to peer-reported trustworthiness, (3) peer-reported trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
5
42
1
1
Order By: Relevance
“…The results from the current study contribute to the growing literature on the importance of trust and trustworthiness for children's psychosocial adjustment (Bernath & Feshbach, 1995;Betts & Rotenberg, 2007a;Betts et al, 2009;Rotenberg et al, 2010;Rotenberg, Boulton, & Fox, 2005;Rotenberg, MacDonald et al, 2004;Rotenberg, McDougall et al, 2004;Rotenberg et al, 2008). Further, the findings of the present study extend previous research by exploring the direct relationship between interpersonal trust consistency and young children's school adjustment over a year.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The results from the current study contribute to the growing literature on the importance of trust and trustworthiness for children's psychosocial adjustment (Bernath & Feshbach, 1995;Betts & Rotenberg, 2007a;Betts et al, 2009;Rotenberg et al, 2010;Rotenberg, Boulton, & Fox, 2005;Rotenberg, MacDonald et al, 2004;Rotenberg, McDougall et al, 2004;Rotenberg et al, 2008). Further, the findings of the present study extend previous research by exploring the direct relationship between interpersonal trust consistency and young children's school adjustment over a year.…”
Section: Discussionsupporting
confidence: 76%
“…Trust is important for relationship formation and maintenance and Rotenberg et al (2008) highlighted the importance of trust for children's preschool adjustment. Further, both positive peer relationships (Johnson, Ironsmith, Snow, & Poteat, 2000) and positive teacher-child relationships (Birch & Ladd, 1997;Howes, Phillipsen, & Peisner-Feinberg, 2000) facilitate Running head: YOUNG CHILDREN'S TRUST CONSISTENCY 20 young children's transition to school and their school adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed actor effects and partner effects as measures of trust beliefs and trustworthiness replicate those found in children from a range of cultures (e.g., . Research has also yielded wide evidence for the reliability and validity of these measures (Rotenberg, Michalik, Eisenberg, & Betts, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The present research focused on the reliability and emotional bases of Rotenberg's (1994Rotenberg's ( , 2010 BDT interpersonal trust framework and operationalized these bases as promisekeeping and secret-keeping trust respectively, because children can readily and reliably report those activities Rotenberg et al, 2008). The present research examined whether: (1) the components of trust could be identified separately in children from the UK, Italy, and Japan using the SRM; (2) at a country level there were gender differences Running head: CROSS-CULTURAL INVESTIGATION OF CHILDREN'S TRUST 10 in the children's trust beliefs and ascribed trustworthiness; and (3) across countries there were variations in the strength of children's trust beliefs and ascribed trustworthiness.…”
Section: Running Head: Cross-cultural Investigation Of Children's Trumentioning
confidence: 99%